All-solid-state-supercapacitor and a process for the fabrication thereof - Kurungot, Sreekumar; Badiger, Manohar V.; Anothumakkool, Bihag; Torris, Arun (WO2014170912 A1, 2014)
The present invention discloses. all-solid-state supercapacitor (ASSP) with enhanced electrode-electrolyte interface which gives highest very high specific capacitance, areal capacitance and shows very low internal resistance (ESR). The invention particularly discloses the fabrication of all-solid-state supercapacitor by intercalation of solid state polymer electrolyte inside the conducting porous substrate coated with a charge storage electrode material to achieve the desired effect.

Architecturally designed Pt-MoS2 and Pt-graphene composites for electrocatalytic methanol oxidation - Patit, Sagar H.; Anothumakkool, Bihag; Sathaye, Shivaram D.; Patil, Kashinath R. (Physical Chemistry Chemical Physics, 2015)
Thin films consisting of platinum nanoparticles (Pt NPs) with uniform size and distribution have been successfully prepared at a liquid-liquid interface. Apart from the usual substrates like glass, Si etc. the films were also deposited on the surfaces of MoS2 thin films and graphene nanosheets (GNS) respectively, by using a layer-by-layer (LbL) deposition technique to form Pt-MoS2 and Pt-GNS composites. The loading concentration of Pt NPs on MoS2 and GNS can be adjusted by selecting the number and sequence of the component layers during LbL deposition. The Pt thin films, Pt-MoS2 and Pt-GNS nanocomposite thin films are characterized using transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), energy dispersive X-ray spectrometry (EDS), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). TEM results of the composites show that Pt NPs with sizes in the range of 1 to 3 nm are uniformly dispersed on the MoS2/GNS surface. The catalytic activities of Pt and Pt-composites for the reaction of methanol oxidation are studied using cyclic voltammetry and chronoamperometry. Electrochemical studies reveal that both the Pt-MoS2 and Pt-GNS nanocomposites show excellent electrocatalytic activity towards methanol oxidation. Pt-MoS2 and Pt-GNS nanocomposite electrodes show excellent stability for reuse of the catalyst. A probable mechanism of catalysis has been discussed. We propose that the similar architecture reported here would be promising for the synthesis of high performance catalysts for fuel cells, gas phase reactions, and other applications such as sensors.